-Subcutaneous tissue of obese children may be too thick for injection solutions to reach intramuscular tissue- - ARSLAN, Filiz; UZUN, Senay; FIDANCI, Berna Eren; TASCILAR, Emre; KORKMAZ, Aysegul; AKYOL, Mesut; ORS, Fatih; Ozgen, Tolga; ÖZGEN, İLKER TOLGA; FIDANCI, Kursat (My University, 2012)
Background: It is very important to measure the subcutaneous tissue thickness of the obese children and choose the appropriate needle length to reach the muscle layer.